(untitled) (TAMADDUN NURI JURNALI, 2025)
As a result of using punctuation as authorial punctuation in the works of poets, deviating from punctuation norms, works are being created in our lyrics that are diverse in both content and form, with high artistry. In the work of the poet S. Ibragimov, one can observe that some signs of pauses become characteristic of the poet’s individual style, turning into a means of creating a poetic image. Punctuation marks play an important role in studying the formal and stylistic features of literary works in Karakalpak lyrics. This, in turn, is a phenomenon related to individual stylistic searches and the creative talent of poets. In the future, there is a need for a deeper study of this important issue.